ปัจจัยที่มีอิทธิพลต่อคุณภาพชีวิตการทำงานของพนักงานโรงพยาบาลบำรุงราษฎร์อินเตอร์เนชั่นแนล - บุรัสกร เตจ๊ะมา (2015)
การวิจัยครั้งนี้เป็นการวิจัยเชิงพรรณนา เพื่อศึกษาความสัมพันธ์ระหว่างคุณลักษณะงาน วัฒนธรรมองค์การกับคุณภาพชีวิตการทำงานของพนักงานโรงพยาบาลบำรุงราษฏร์อินเตอร์เนชั่นแนล กลุ่มตัวอย่างคือพนักงานระดับปฏิบัติการจำนวน 252 คน การสุ่มตัวอย่างใช้วิธีการสุ่มแบบมีระบบ โดยการสุ่มตัวอย่างแบบไม่แทนที่ ใช้แบบสอบถามเป็นเครื่องมือในการเก็บรวบรวมข้อมูล แบบสอบถามได้คืนมาร้อยละ 94.44 สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ ร้อยละ ความถี่ ค่าเฉลี่ย และวิเคราะห์ความสัมพันธ์ระหว่างคุณลักษณะงาน บรรยากาศองค์การ และคุณภาพชีวิตการทำงานโดยใช้สถิติสหสัมพันธ์แบบเพียร์สัน ผลการวิจัยพบว่าพนักงานมีระดับคุณภาพชีวิตและคุณลักษณะงานอยู่ในระดับ ปานกลาง และบรรยากาศองค์การอยู่ในระดับมาก คุณลักษณะงานมีความสัมพันธ์กับคุณภาพชีวิตการทำงานเชิงบวกอยู่ในระดับปานกลางอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 และบรรยากาศองค์การมีความสัมพันธ์เชิงบวกกับคุณภาพชีวิตการทำงาน ในระดับมากอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 ผลการวิจัยเสนอแนะให้ผู้บริหารควรพิจารณาสนับสนุนปัจจัยต่างๆ โดยการให้รางวัลเมื่อพนักงานปฏิบัติงานได้ดีและส่งเสริมให้พนักงานมีกิจกรรมร่วมกันเพื่อสร้างสัมพันธภาพที่ดีระหว่างผู้ปฏิบัติงานเพื่อให้คุณภาพชีวิตในการทำงานของพนักงานระดับปฏิบัติการมีระดับที่สูงขึ้น This research is a descriptive research. The purpose of this research was to study the relationship between job characteristics, organizational climate, and the quality of working life. The sample group for this research comprised of 252 staff of Bumrungrad International Hospital. A questionnaire was used to collect the data. The sample group was selected by systematic sampling without replacement and 94.44 percent of questionnaires were completed and collected. The data were then analyzed and summarized in terms of percentage, frequency, and mean. Pearson’s product - moment correlation effi cient was used to analyze the data. The results revealed that the staff had a quality of working life at a moderate level. Overall job characteristics were at a moderate level, whereas the organizational climate was at a high level. Job characteristics showed a moderate positive relationship with the quality of working life and were statistically signifi cant at the level of 0.05, while the organizational climate had a high positive relationship with the quality of working life that was statistically signifi cant at the level of 0.05 as well. Administrators should support any factor that encourages the quality of working life of staff. To promote the quality of working life of staff to a high level, the recognition and encouragement should be given by working together in order to create a good relationship and to raise their quality of working life.